Facial nerve regeneration using silicone conduits filled with ammonia-functionalized graphene oxide and frankincense-embedded hydrogel - Sepehr Aghajanian; Aliasghar Taghi Doulabi; Masoume Akhbari; Alireza Shams (BMC, 2021)
Abstract Background Silicone tube (ST) conduits have been accepted as a therapeutic alternative to direct nerve suturing in the treatment of nerve injuries; however, the search for optimal adjuncts to maximize the outcomes is still ongoing. Frankincense (Fr) and graphene oxide (GO) have both been cited as neuroregenerative compounds in the literature. This study assesses the efficacy of these materials using a ST conduit in a rat facial nerve motor neuron axotomy model, distal to the stylomastoid foramen. Methods Ammonia-functionalized graphene oxide (NH2-GO) and/or Fr extract were embedded in a collagen-chitosan hydrogel and were injected inside a ST. The ST was inserted in the gap between the axotomized nerve stumps. Return of function in eye closure, blinking reflex, and vibrissae movements were assessed and compared to control groups through 30 days following axotomy. To assess the histological properties of regenerated nerves, biopsies were harvested distal to the axotomy site and were visualized through light and fluorescence microscopy using LFB and anti-MBP marker, respectively. Results There was no significant difference in behavioral test results between groups. Histological analysis of the nerve sections revealed increased number of regenerating axons and mean axon diameter in NH2-GO group and decreased myelin surface area in Fr group. Using both NH2-GO and Fr resulted in increased number of regenerated axons and myelin thickness compared to the hydrogel group. Conclusions The findings suggest a synergistic effect of the substances above in axon regrowth, notably in myelin regeneration, where Fr supposedly decreases myelin synthesis.